2012
DOI: 10.1007/s00268-012-1714-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Primary Hepatic Epithelioid Hemangioendothelioma: Retrospective Study of 33 Patients

Abstract: Liver resection and TACE have comparable outcomes in HEHE patients. The presence of symptoms indicates a poor prognosis. Older age and elevated serum CA19-9 are potential negative impact factors on outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 25 publications
(44 reference statements)
2
26
0
2
Order By: Relevance
“…HEHE is resistant to chemotherapy and radiotherapy, thus, complete surgical resection is performed in patients with early stage monolobar disease, and liver transplantation is the only curative treatment in specific patients with diffuse liver involvement[7-9]. However, HEHE commonly presents nonspecific and variable clinical manifestations, ranging from asymptomatic to portal hypertension, Budd-Chiari syndrome or hepatic failure[10,11]. In addition, laboratory measurements also lack specificity in the diagnosis of HEHE, which typically manifests as a “halo” sign and “capsular retraction” on imaging[3,12].…”
Section: To the Editormentioning
confidence: 99%
“…HEHE is resistant to chemotherapy and radiotherapy, thus, complete surgical resection is performed in patients with early stage monolobar disease, and liver transplantation is the only curative treatment in specific patients with diffuse liver involvement[7-9]. However, HEHE commonly presents nonspecific and variable clinical manifestations, ranging from asymptomatic to portal hypertension, Budd-Chiari syndrome or hepatic failure[10,11]. In addition, laboratory measurements also lack specificity in the diagnosis of HEHE, which typically manifests as a “halo” sign and “capsular retraction” on imaging[3,12].…”
Section: To the Editormentioning
confidence: 99%
“…In our series, two of eight patients (25%) suffered from extra hepatic metastasis upon time of resection, the percentage reported in literature ranging from 16.9% to 36.6% [9], [16], [17], [18], [19]; in some series only resected patients, in other only transplanted patients, and in others patients treated with various approaches are reported. Presence of extra hepatic disease, however, is not always a contraindication for resection, as shown by the course of the two patients reported here and in other series [16], [17], [18], [19]. An individual treatment strategy has to be created for each individual patient after interdisciplinary discussion of the patient and the biological characteristics of the tumor.…”
Section: Discussionmentioning
confidence: 44%
“…Due to the rarity of the disease and the heterogeneity of inclusion criteria and therapies applied, survival rates reported in literature vary considerably, ranging from 88 to 100% one year and 43–83% five years after therapy [5], [18], [19], [28], [29], [30]. In our patients, median survival is 100 months today (48–266), with all eight patients being alive.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The management options for HEHE include liver resection, LT, chemotherapy, radiotherapy, immunotherapy, or follow-up alone. The prognostic factors of HEHE are unclear, even if some authors have reported that the presence of symptoms, older age, and elevated serum CA19-9 negatively affect the outcome 13 . Furthermore, Cardinal et al 14 found that the presence of extrahepatic disease beyond regional portal nodes was a negative predictor of outcome.…”
Section: Discussionmentioning
confidence: 99%